Development of a Problem-Based Learning (PBL)-Based E-Book on Kodular to Improve Students' Cognitive Abilities - Ekabriyanti Reni Oktafia; Yeri Sutopo; Ade Novi Nurul Ihsani; Basyirun Basyirun (Journal of Vocational and Career Education, 2026)
The rapid development of information and communication technology requires innovation in learning resources, particularly in Informatics education at the senior high school level. This study aims to develop a Problem-Based Learning (PBL)-based e-book integrated with Kodular and to examine its feasibility, practicality, and effectiveness in improving students’ cognitive abilities. This research employed a Research and Development approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The e-book was implemented with 27 eleventh-grade students of SMA Negeri 2 Blora as the experimental group and students of SMA Negeri Jepon Blora as the control group. Data were collected through expert validation questionnaires, teacher response questionnaires, and cognitive ability tests. The results show that the developed e-book is highly feasible and practical for use in Informatics learning. Furthermore, statistical analysis indicates that students who used the PBL-based Kodular e-book achieved significantly higher cognitive gains than those who learned using conventional materials. These findings suggest that integrating PBL with visual programming platforms such as Kodular in digital learning resources can effectively enhance students’ cognitive performance in Informatics education.